Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1017/s0952675718000209
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm uniformity bias in the learning of Korean verbal inflections

Abstract: This study explores the role of paradigm uniformity bias in the acquisition of Korean verbal inflections. Paradigm uniformity bias has been proposed in a constraint-based phonological framework, but has rarely been supported by experimental data. This paper provides experimental evidence for paradigm uniformity bias from four- to seven-year-old Korean children learning their native language phonology. Experiment 1 demonstrates that children alter morphological structures in order to produce non-alternating ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…And all fillers showed no alternation of the consonants, so in a language as a whole only 25% of data exhibited /n/~/l/ alternation across all of the four artificial languages. Previous studies revealed a strong bias against alternation, even when 75% of the training data showed alternation (Coetzee, 2009;White, 2014;Do, 2018). Therefore, the low alternation rates in the current study are not unusual.…”
Section: General Discussion and Conclusionsupporting
confidence: 45%
See 1 more Smart Citation
“…And all fillers showed no alternation of the consonants, so in a language as a whole only 25% of data exhibited /n/~/l/ alternation across all of the four artificial languages. Previous studies revealed a strong bias against alternation, even when 75% of the training data showed alternation (Coetzee, 2009;White, 2014;Do, 2018). Therefore, the low alternation rates in the current study are not unusual.…”
Section: General Discussion and Conclusionsupporting
confidence: 45%
“…Even in categorical learning conditions, where all critical items always alternated before nonhigh front vowels (CNL) or high front vowels (CUL), the tendency to alternate was low. This could presumably be due to half of the non-alternating items in the other phonological contexts, i.e., high front vowels in CNL and non-high-front vowels in CUL, which could also suggest a strong bias against alternation across the experimental conditions (Wilson, 2003(Wilson, , 2006Tessier, 2012;Do, 2018). We then compared the alternation rates within categorical vs. variable pattern learning conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Paradigm uniformity is the well-established preference for an underlying morpheme to have identical exponents (Kiparsky 1982: ch. 11, Steriade 2000, Do 2018). This constraint assigns a violation for every form in the comparison set that shares a morpheme with the candidate but not its surface realisation.…”
Section: Corpus Studymentioning
confidence: 99%
“…For example, the final /t/ phoneme of the verb stem pat becomes 'flapped' in American English when the -ing suffix is added (patting). Previous studies have suggested that phonological alternations are initially disfavored by learners, in artificial language learning experiments with adults and children (Kapatsinski, 2009;Smolek, 2019;Smolek & Kapatsinski, 2018;Stave, Smolek, & Kapatsinski, 2013;Tessier, 2012;White, 2013White, , 2014 as well as in children's natural language acquisition (Do, 2018;Kerkhoff, 2007). The second factor we consider is homophony avoidance.…”
Section: Introductionmentioning
confidence: 99%